Fully Solution‐Processed Photonic Structures from Inorganic/Organic Molecular Hybrid Materials and Commodity Polymers. (28th January 2019) - Bachevillier, Stefan; Yuan, Hua‐Kang; Strang, Andrew; Levitsky, Artem; Frey, Gitti L.; Hafner, Andreas; Bradley, Donal D. C.; Stavrinou, Paul N.; Stingelin, Natalie
Abstract: Managing the interference effects from thin (multi‐)layers allows for the control of the optical transmittance/reflectance of widely used and technologically significant structures such as antireflection coatings (ARCs) and distributed Bragg reflectors (DBRs). These rely on the destructive/constructive interference between incident, reflected, and transmitted radiation. While known for over a century and having been extremely well investigated, the emergence of printable and large‐area electronics brings a new emphasis: the development of materials capable of transferring well‐established ideas to a solution‐based production. Here, demonstrated is the solution‐fabrication of ARCs and DBRs utilizing alternating layers of commodity plastics and recently developed organic/inorganic hybrid materials comprised of poly(vinyl alcohol) (PVAl), cross‐linked with titanium oxide hydrates. Dip‐coated ARCs exhibit an 88% reduction in reflectance across the visible compared to uncoated glass, and fully solution‐coated DBRs provide a reflection of >99% across a 100 nm spectral band in the visible region. Detailed comparisons with transfermatrix methods (TMM) highlight their excellent optical quality including extremely low optical losses. Beneficially, when exposed to elevated temperatures, the hybrid material can display a notable, reproducible, and irreversible change in refractive index and film thickness while maintaining excellent optical performance allowing postdeposition tuning, e.g., for thermo‐responsive applications, including security features and product‐storage environment monitoring. Abstract : Fully printed antireflection coatings Printable Photonics (ARCs) and distributed Bragg reflectors (DBRs) with a reflection <1% over the visible range and >99% across a 100 nm reflectance band are demonstrated. With the use of a tunable inorganic/polymer hybrid, the DBR is thermo‐responsive with a stop‐band blue‐shifting by 150 nm. The development of printable photonics is an enabling step for low‐cost and large‐area applications.